PENGARUH SUSTAINABILITY REPORTING, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP NILAI PERUSAHAAN SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2025 - Ririn Fatmawati; Hestin Sri Widiawati; Erna Puspita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Firm value is an important indicator that reflects a company's success in enhancing shareholder wealth and attracting investors. This study aims to examine the effect of sustainability reporting, firm size, and leverage on firm value in transportation sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2025 period. This study employed a quantitative approach using a purposive sampling technique. Data were obtained from the companies' annual reports and sustainability reports and were analyzed using classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results show that sustainability reporting has no significant effect on firm value. Firm size has a significant effect on firm value, while leverage also has a significant effect on firm value. Simultaneously, sustainability reporting, firm size, and leverage have a significant effect on firm value. Therefore, leverage is the most dominant variable affecting firm value, whereas sustainability reporting has not been able to influence firm value in transportation sector companies listed on the Indonesia Stock Exchange during the 2022–2025 period.